Financial situation and challenges for management of SME hospitals: evidence from Poland - Szewieczek, Aleksandra (Serbian Journal of Management, 2021)
The hospital represents a specific organisation, operating in a turbulent environment and financed to a large extent by public funds. The health sector is exposed to constant political and social pressure. This causes significant problems with maintaining its financial stability, which particularly affects hospitals in the SME sector.The aim of this paper is to examine the relationship between selected financial indicators and some environmental phenomena that affect the financial situation and future financial stability of a selected group of hospitals from the SME group. The results will also be compared to the situation of other SME entities. The research is based on descriptive analysis, descriptive statistics, and correlation analysis of selected data.The results indicate that the financial situation of hospitals belonging to the SME group differs significantly from the overall SME sector, and does not bode positively for their future development. The current financial situation presents particular challenges for managers in balancing financial streams and ensuring economic sustainability. At the same time, this situation should encourage decision-makers to ensure an adequate level of revenues for these public service providers, as well as face other challenges related to operational management.
Keywords: management; hospital; health care; finance; analysis; SME